Algorithm of the numerical solution of the multidimensional inverse problem of electrodynamics - Iskakov, K.T.; Kussainova, А.Т.; Khassenova, Z.T. (Bulletin of the Karaganda University. Mathematics Series, 2017)
In this article, we consider the inverse coeﬃcient problem for the multidimensional equation of electrodynamics in the linear approximation. To solve the coeﬃcient inverse problem for determining the conductivity of a medium that depends on two variables, an optimization method is used. A formula is obtained for calculating the gradient of the functional. The corresponding conjugate problems are formulated.